2017
DOI: 10.1186/s12889-017-4013-5
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the London Exercise and Pregnant (LEAP) Smokers randomised controlled trial process evaluation: implications for the design of physical activity for smoking cessation interventions during pregnancy

Abstract: BackgroundThe challenges of delivering interventions for pregnant smokers have been poorly documented. Also, the process of promoting a physical activity intervention for pregnant smokers has not been previously recorded. This study describes the experiences of researchers conducting a randomised controlled trial of physical activity as an aid to smoking cessation during pregnancy and explores how the effectiveness of future interventions could be improved.MethodsTwo focus groups, with independent facilitators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…(Mohsin and Bauman, 2005) In fact, low-income women commonly have the lowest utilization of smoking cessation counseling services (Scheuermann et al, 2017) and interventions have been developed and evaluated to promote smoking cessation among pregnant women (Naughton et al, 2017). Most recently, smoking cessation interventions with a physical activity component targeting pregnant women have been suggested, interventions supplementing smoking cessation materials with text messaging, as well as broadening the scope of smoking screening programs to include general practitioners and obstetricians have been suggested (Giatras et al, 2017; Zeev et al, 2017; Naughton et al, 2017). Further, although smoking cessation in pregnancy has been associated with decreased depressive symptoms, implying a further benefit of large-scale smoking cessation programs, large-scale community-based trials that target depression reduction to improve smoking cessation rates among pregnant women at a population level have not been conducted (Munafo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(Mohsin and Bauman, 2005) In fact, low-income women commonly have the lowest utilization of smoking cessation counseling services (Scheuermann et al, 2017) and interventions have been developed and evaluated to promote smoking cessation among pregnant women (Naughton et al, 2017). Most recently, smoking cessation interventions with a physical activity component targeting pregnant women have been suggested, interventions supplementing smoking cessation materials with text messaging, as well as broadening the scope of smoking screening programs to include general practitioners and obstetricians have been suggested (Giatras et al, 2017; Zeev et al, 2017; Naughton et al, 2017). Further, although smoking cessation in pregnancy has been associated with decreased depressive symptoms, implying a further benefit of large-scale smoking cessation programs, large-scale community-based trials that target depression reduction to improve smoking cessation rates among pregnant women at a population level have not been conducted (Munafo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[...] During prenatal care, a window of opportunity for smoking cessation/reduction is opened, since there is a strong sense of guilt that causes the woman to seek to justify smoking, demonstrating that despite smoking, she is aware of the harmful effects showed that the intervention was beneficial in smoking cessation reduction/cessation. It was also considered relevant to involve family and friends as partners for more effective action (21) . Interventions for smoking cessation should go beyond biomedical and behavioral approaches, acting in community life with intersectoral actions.…”
Section: Discussionmentioning
confidence: 99%
“…DL is a female doctoral student in Community Health Education with a Master’s degree in Public Health and more than three years of qualitative research experience in one-on-one and focus group interviewing. She moderated the sessions using a focus group discussion guide informed by prior qualitative work among research staff [14, 17] The focus group began with an introduction where DL described her background, interest in the topic, and reasons for conducting the research. Following this introduction, open-ended questions were used to understand the health educators’ and interviewers’ perspectives on implementing this lifestyle intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Lifestyle interventions regularly rely on study staff to implement the intervention and collect outcomes data directly from study participants. To date, little has been done to identify the individual components of lifestyle interventions, and the aspects of their implementation, that are critical to success [1416]. Qualitative research tools can identify staff persons’ experiences and knowledge that might otherwise remain hidden through more traditional quantitative measures [17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation